Human C-terminally truncated ERα variants resulting from the use of alternative exons in the ligand-binding domain. (15th April 2016) - Hattori, Yujiro; Ishii, Hirotaka; Munetomo, Arisa; Watanabe, Hiroshi; Morita, Akio; Sakuma, Yasuo; Ozawa, Hitoshi
Abstract: The nuclear receptor genes contain alternative internal and terminal exons, with alternative exon incorporation yielding mRNA variants that encode various receptor types, including some with C-terminal truncation that exhibit constitutive activation or dominant-negative transcriptional transactivation. However, C-terminally truncated estrogen receptor α (ERα) variants with alternative sequences have rarely been reported in humans. Therefore, we assessed human ERα genomic organization and alternative splicing profiles, and identified both alternative exons and C-terminally truncated ERα variants. These naturally occurring C-terminally truncated ERα proteins were localized in the nuclei of transfected cells. In addition, ERαi45c and ERαΔ5 variants exhibited constitutive transactivation of an estrogen responsive element-driven promoter in transfected cells. We manufactured expression vectors encoding artificially truncated ERα constructs and evaluated their transactivation abilities to establish mechanisms determining the constitutive activity and dominant-negative properties of truncated variants. Lack of the region encoded in exon 8 eliminated basal and ligand-induced transcriptional transactivation. The C-terminally truncated ERα variants/constructs containing the helices 5 in their ligand-binding domains did not exhibit constitutive transactivation. Furthermore, we demonstrated that truncation from C-termini to helices 5 in the variant ligand-binding domains was required for constitutive activation and found that the remnant regions of the ligand-binding domains and variant-specific sequences influenced transcriptional transactivation efficiency. In conclusion, we elucidated the structural and functional features of novel C-terminally truncated ERα variants and revealed the mechanisms underlying constitutive transactivation by C-terminally truncated nuclear receptor variants. Highlights: Novel C-terminally truncated ERα variants were identified in humans. Some variants exhibited constitutive transactivation in transfected cells. The primary variant mechanism of activation is deletion of helix 5. The C-terminal regions of the variants influence the efficiency of transactivation. These new findings help advance ERα variant research.